Aberrant Gut-To-Brain Signaling in Irritable Bowel Syndrome - The Role of Bile Acids - Ní Dhonnabháín, Róisín; Xiao, Qiao; O’Malley, Dervla (Frontiers in Endocrinology, 2021)
Functional bowel disorders such as irritable bowel syndrome (IBS) are common, multifactorial and have a major impact on the quality of life of individuals diagnosed with the condition. Heterogeneity in symptom manifestation, which includes changes in bowel habit and visceral pain sensitivity, are an indication of the complexity of the underlying pathophysiology. It is accepted that dysfunctional gut-brain communication, which incorporates efferent and afferent branches of the peripheral nervous system, circulating endocrine hormones and local paracrine and neurocrine factors, such as host and microbially-derived signaling molecules, underpins symptom manifestation. This review will focus on the potential role of hepatic bile acids in modulating gut-to-brain signaling in IBS patients. Bile acids are amphipathic molecules synthesized in the liver, which facilitate digestion and absorption of dietary lipids. They are also important bioactive signaling molecules however, binding to bile acid receptors which are expressed on many different cell types. Bile acids have potent anti-microbial actions and thereby shape intestinal bacterial profiles. In turn, bacteria with bile salt hydrolase activity initiate the critical first step in transforming primary bile acids into secondary bile acids. Individuals with IBS are reported to have altered microbial profiles and modified bile acid pools. We have assessed the evidence to support a role for bile acids in the pathophysiology underlying the manifestation of IBS symptoms.